Outcomes of dialysis and the transplantation options for patients with diabetic end‐stage renal disease in Korea. Issue 5 (11th March 2016) - Jeon, Hee Jung; Koo, Tai Yeon; Han, Miyeun; Kim, Ha Jin; Jeong, Jong Cheol; Park, Hyojun; Ha, Jongwon; Kim, Sung Joo; Ahn, Curie; Park, Jae Berm; Yang, Jaeseok
Abstract: Background: The best therapeutic option for diabetic end‐stage renal disease (DMESRD) has not been established among living donor kidney transplantation (LDKT), deceased donor kidney transplantation (DDKT), simultaneous pancreas and kidney transplantation (SPK), and dialysis. Methods: We retrospectively analyzed the outcomes of DMESRD patients at two Korean centers from February 2000 to December 2011. Results: Among 674 patients, 295 underwent kidney transplantation (LDKT, 175; DDKT, 72; and SPK, 48), while 379 were still on dialysis. The dialysis group had a higher mortality rate than the transplantation group. From the time after dialysis initiation, LDKT group had a better patient survival rate than DDKT registration group and SPK registration group. From the time after transplantation, LDKT had a better patient survival rate than DDKT; however, there was no significant difference between LDKT and SPK. In SPK, patient survival and kidney or pancreas graft survival rates were not different between types 1 and 2 DMESRD. Conclusion: LDKT is better than waiting for SPK/DDKT in DMESRD patients, if a living donor is available, and this conclusion may be unique to Korea where waiting time for SPK is long. SPK can be used in non‐obese Asians with type 2 as well as type 1 DMESRD.